Comparison of Efficacy of Luliconazole 1% w/w Cream Versus Amorolfine 0.25% w/w Cream in the Treatment of Tinea cruris: A Single-center, Randomized, Double-blind, Non-inferiority Study - Abhipsa Samal; Bhabani S.T.P. Singh; Bikash Ranjan Kar; Liza Mohapatra (Journal of Pure and Applied Microbiology)
Dermatophytosis is a superficial fungal infection involving the keratinized tissues. Limited dermatophytosis is usually treated with topical antifungals. Amorolfine and luliconazole are relatively newer and superior topical antifungals much in use in recent times. To study the therapeutic efficacy and safety of luliconazole 1% and amorolfine 0.25% cream in patients with tinea cruris. A single-center, randomized, double-blind, non-inferiority study comparing luliconazole and amorolfine was conducted on patients with localized tinea cruris. 81 patients completed the study, with 40 patients treated with luliconazole and 41 patients treated with amorolfine. Both groups of patients were followed up at the end of 2 weeks. No statistically significant difference was found between luliconazole and amorolfine regarding improvement in erythema, scaling, pruritus, and mycological cure. Both the medications were safe and well tolerated by the patients. The duration of the study was short, and there was no long-term follow-up. Amorolfine is not inferior to luliconazole in treating limited tinea cruris.